Effectiveness of a chest physiotherapy care map in hospitalized patients - T. Sereearuno (2020)
© 2020 Background:: Conventional chest physiotherapy (chest PT) has been widely used to facilitate airway clearance. However, conventional chest PT is time consuming, unnecessary prescriptions result in heavier workloads for therapists. Therefore, judicious prescription of chest PT is important. Purpose:: To develop a chest physiotherapy care-map and evaluate its efficacy. Method:: Seventy-eight hospitalized patients who were consulted for chest PT were enrolled and consecutively allocated into two groups of 39 patients. Group I and II was enrolled before and after the implementation of the chest PT map, respectively. Result:: After the care-map was implemented, the chest PT prescription rate decreased from 56.4% to 33.3%, (p = 0.040). The duration of conventional chest PT trended to lower but not reaching significance from 4.5 (1–28) to 4 (2–9) days, (p = 0.582). The mean cost of chest PT was reduced by 38.2% (p = 0.019). Conclusion:: Chest PT care-map is an effective tool to reduce unnecessary chest PT prescriptions, lower costs, and more effectively allocate therapist time.